Ethics, governance and corporate crime challenges and consequences - Said, Roshima; Crowther, David; Amran, Azlan (Developments in corporate governance and responsibility, 2014)
This book is comprised of academic work on key current issues pertaining to the areas of ethics, governance and corporate crimes. The book provides a platform for researchers to publish their work, articulate their concerns and offer critical perspectives on what they see happening around them.